# How do you simplify #e^(1 + ln x)#?

##### 1 Answer

Write your answer here...

Start with a one sentence answer

Then teach the underlying concepts

Don't copy without citing sources

preview

?

#### Answer

Write a one sentence answer...

#### Answer:

#### Explanation

Explain in detail...

#### Explanation:

I want someone to double check my answer

mason m
Share

Mar 3, 2016

#### Answer:

#### Explanation:

Use the rule to split up the exponent:

#a^(b+c)=a^b(a^c)#

Thus:

#e^(1+lnx)=e^1(e^lnx)#

Here:

#e^1=e#

#e^lnx=x#

So:

#e^(1+lnx)=e*x#

Was this helpful? Let the contributor know!

Describe your changes (optional) 200